2003
DOI: 10.1088/0953-8984/15/19/333
|View full text |Cite
|
Sign up to set email alerts
|

Photoreflectance studies of optical transitions in type II (GaAs)m(AlAs)nsuperlattices

Abstract: Photoreflectance (PR) spectra of two type II [001](GaAs)m(AlAs)n superlattices (SLs) have been measured at 77 K. In the conventional picture of the envelope-function approximation, the lowest conduction state originates, in the first sample, from the Xz point of the AlAs Brillouin zone (z being the growth direction) whereas it originates from the Xx,y point in the second sample. Our spectra exhibit Franz–Keldysh oscillation (FKO) features and interband transition lines. The origin of the built-in electric fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…At the same time, the concentration of pyrolysis carbon atoms landing on the catalyst cracking surface was high and it is easy to cause the local concentration of pyrolysis carbon atoms saturated, thus forming amorphous carbon and causing the catalyst deactivated through encapsulation, as observed that low yield CNTs corresponding with large amounts of amorphous carbons were formed. [ 54 ] With the increase of temperature to 650 °C, more obvious CNT growth was observed all over the CF surface. At 750 °C, both the diameter and the length of CNTs dramatically increased, indicating the catalyst is highly efficient and durable at this critical temperature.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the concentration of pyrolysis carbon atoms landing on the catalyst cracking surface was high and it is easy to cause the local concentration of pyrolysis carbon atoms saturated, thus forming amorphous carbon and causing the catalyst deactivated through encapsulation, as observed that low yield CNTs corresponding with large amounts of amorphous carbons were formed. [ 54 ] With the increase of temperature to 650 °C, more obvious CNT growth was observed all over the CF surface. At 750 °C, both the diameter and the length of CNTs dramatically increased, indicating the catalyst is highly efficient and durable at this critical temperature.…”
Section: Resultsmentioning
confidence: 99%